Stunting predictors among children aged 6-23 months in the urban area of Garut Kota Subdistrict, Indonesia - Yuliasih, Yuneu; Setyaningtyas, Dian Eka; Ipa, Mara (Universitas Gadjah Mada, 2024)
Purpose: Stunting remains a public health and nutrition problem in Indonesia. Stunting is widespread in rural areas, but information on stunting in urban areas is limited. This study aims to determine the risk factors for stunting in children aged 6–23 months in Garut Kota Subdistrict, Garut Regency, West Java, Indonesia. Method: A cross-sectional study was conducted between April and July 2021 on 93 children aged 6–23 months in Garut Kota Subdistrict. Child, parental, and household variables were analyzed, and logistic regression was conducted to assess the predictors of stunting. Results: Of the 93 children examined, 40 (43%) were classified as stunted. The studies revealed predictors of stunting in the Garut Kota Subdistrict urban region among children under two years old. Stunted children were 0.065 times less likely to have fathers with middle-to-upper-class education (AOR = 0.065; 95% CI: 0.005-0.932). Stunting is less common in children whose homes have access to better drinking water (AOR = 0.268, 95% CI: 0.078–0.915). Furthermore, children from smokers' households were 0.012 times more likely to be stunted (AOR = 0.012; 95% CI: 0.001-0.238). Conclusion: Father's education level, access to adequate drinking water, and the presence of family members who smoke are factors that influence the prevalence of stunting in children aged 6-23 months in Garut Kota Subdistrict. A comprehensive, multisectoral program needs to boost family income, provide clean, safe drinking water that is easily accessible, and reduce household smoking to decrease the prevalence of stunting in children.